2015
DOI: 10.1371/journal.pone.0126986
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analyses Point to Candidate Genes for Electric Shock Avoidance in Drosophila melanogaster

Abstract: Electric shock is a common stimulus for nociception-research and the most widely used reinforcement in aversive associative learning experiments. Yet, nothing is known about the mechanisms it recruits at the periphery. To help fill this gap, we undertook a genome-wide association analysis using 38 inbred Drosophila melanogaster strains, which avoided shock to varying extents. We identified 514 genes whose expression levels and/ or sequences co-varied with shock avoidance scores. We independently scrutinized 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…Furthermore, we found strong enrichment of Nowl in Rdl-expressing MB neurons, consistent with Nowl's functioning in the regulation of sleep via wake-promoting neurons in the mushroom body. Interestingly, nowl was also identified in an olfactory-learning screen, in which it was found to inhibit electric-shockreinforced associative learning, consistent with a role for nowl in mushroom-body neuronal function [25]. Furthermore, we observed that Nf1 knockdown in Rdl-expressing neurons caused sleep reduction and fragmentation of night-time sleep similar to nowl knockdown, further supporting an interaction between Nf1 and nowl in the regulation of sleep.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Furthermore, we found strong enrichment of Nowl in Rdl-expressing MB neurons, consistent with Nowl's functioning in the regulation of sleep via wake-promoting neurons in the mushroom body. Interestingly, nowl was also identified in an olfactory-learning screen, in which it was found to inhibit electric-shockreinforced associative learning, consistent with a role for nowl in mushroom-body neuronal function [25]. Furthermore, we observed that Nf1 knockdown in Rdl-expressing neurons caused sleep reduction and fragmentation of night-time sleep similar to nowl knockdown, further supporting an interaction between Nf1 and nowl in the regulation of sleep.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, night-time sleep dropped dramatically in both males and females. Loss of one copy of nowl (on the X chromosome) in females did not elicit a phenotype, suggesting that the nowl 1 mutation is a recessive loss-of-function allele, consistent with the transcript-level defect previously reported [25]. To further confirm these results, we generated a CRISPR/Cas9-mediated deletion of the nowl coding sequence.…”
Section: Nowl Is Required For Night-time Sleepsupporting
confidence: 77%
See 1 more Smart Citation
“…This gene is primarily involved in the formation of hairs. 73 Appel et al 95 ). An RNAi screen specific to neurons identified ergic53 as a candidate gene involved in the perception of very high temperatures.…”
Section: Identification Of Candidate Genesmentioning
confidence: 99%
“…Both of these are significant only between the learning cohorts, with higher expression in the high learning cohort (Obp28a: Individual QTL BCI regions showing possible candidate genes. Appel et al95 also found evidence for a role of the genes influencing mechanosensory bristles and electric shock avoidance in a different D melanogaster mapping population, the DGRP. When a peak is shared between learning and memory, both BCIs are shown.…”
mentioning
confidence: 96%